My brother the frog - Lindquist, R. C.; Coutts, Lisa (Macmillan Education Australia South Yarra [Vic.], 1999)
My Brother the Frog is a whimsical children's story about a young boy who imagines his brother as a frog. Through imaginative illustrations and playful storytelling, the narrative explores themes of sibling relationships, creativity, and the magic of childhood imagination. As the boy navigates his adventures with his froggy brother, readers are invited to embrace the wonders of fantasy and the bond between siblings. This charming tale encourages creativity and offers a delightful perspective on family dynamics.